Tool for Transformation: Cooperative Inquiry as a Process for Healing from Internalized Oppression - Penny Rosenwasser (Adult Education Research Conference, 2000)
This paper documents how cooperative inquiry can be a transformative tool for groups – in this case, a diverse group of Jewish women – to make meaning from their experience of internalized oppression and to create healing strategies.